2001
DOI: 10.1002/ijc.1399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of estrogen-dependent breast cell responses with phenylacetate

Abstract: The aromatic fatty acid phenylacetate (PA) and its analogs have come under intense investigation due to their ability to cause the growth arrest of a variety of neoplasia, including human breast cancer. We have determined that PA and its halide derivative 4-chlorophenylacetate (4-CPA) showed marked antiproliferative activity on 3 of 6 human breast cancer cell lines tested. Interestingly, the 3 cell lines that were growth inhibited by PA and 4-CPA were estrogen receptor (ER) positive (T47-D, MCF-7 and ZR-75-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…In contrast, cultures grown in the presence of arginine butyrate demonstrated a decrease in colony number relative to control conditions. Hematopoietic cytokines, including erythropoietin, effect their survival (anti-apoptotic) activity by altering the ratios of Bcl-2 family pro-apoptotic and anti-apoptotic proteins in the cell, particularly Bcl-x and Mcl-1 [21][22][23][24][25][26][27]. We therefore examined Bcl-2 family protein expression in 32D cells cultured under extremely low IL-3 conditions ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, cultures grown in the presence of arginine butyrate demonstrated a decrease in colony number relative to control conditions. Hematopoietic cytokines, including erythropoietin, effect their survival (anti-apoptotic) activity by altering the ratios of Bcl-2 family pro-apoptotic and anti-apoptotic proteins in the cell, particularly Bcl-x and Mcl-1 [21][22][23][24][25][26][27]. We therefore examined Bcl-2 family protein expression in 32D cells cultured under extremely low IL-3 conditions ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids The plasmid ERE v -tk-Luc, which was used to monitor the ER transactivation, contains the vitellogenin A2 ERE sequence from À336 to À310 inserted upstream of the herpes simplex virus thymidine kinase promoter and has been described previously (22,23). The pGL3-promoter vector was purchased from Promega and contains an SV40 promoter of 202 bp upstream of the luciferase gene with no transcription factor binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…Gliozzo et al (1998) reported that cultured MDA-MB-157 cells, which do not express ER (Sawatsri et al (2001), showed a strong mitogenic response to exogenous insulin. This stimulation was suppressed by a pharmacological inhibitor of MAPK kinase, which phosphorylates and activates MAPK (Fig.…”
Section: Breast Cancer Cell Ir and Mitosismentioning
confidence: 99%